18th IEEE International Symposium on Power Line Communications and Its Applications 2014
DOI: 10.1109/isplc.2014.6812326
|View full text |Cite
|
Sign up to set email alerts
|

A measurement-based model of energy consumption for PLC modems

Abstract: Abstract-In this paper a detailed measurements-based analysis of the energy consumption of commercial broadband PLC modems is reported. Energy consumption measurements are carried out on the basis of pairs of many commercial PLC modems. Ethernet frames with variable sizes and bit/frame rates are sent on a modem, and received on the other modem. An analytic linear model that quantifies the energy consumption associated to Ethernet frames and PLC Physical Blocks (PBs) processing is proposed for a pair of PLC mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Based on the preceding measurements and following the same approach as in [6], we propose the following linear model of energy consumption for MIMO PLC modems. The total power consumption at the transmitter and the receiver are respectively given by…”
Section: Power Consumption Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the preceding measurements and following the same approach as in [6], we propose the following linear model of energy consumption for MIMO PLC modems. The total power consumption at the transmitter and the receiver are respectively given by…”
Section: Power Consumption Modelmentioning
confidence: 99%
“…Therefore, the development of the new generation of PLC technologies requires further research efforts for investigating the electric power consumption of MIMO PLC devices. Regarding traditional SISO PLC modems, the energy evaluations in [6] showed that the total power consumption P for communication between a pair of PLC modems is defined as follows…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to achieve best energy efficiency, extensive simulations are conducted solving the optimization problem of the energyharvesting time factor in several scenarios. For a more realistic power consumption scenario, we incorporate the dynamic power, static power and idle power of PLC modems in our power consumption profile; similar to [10] and [9]. The results reveal that the proposed system is able to offer remarkable energy efficiency enhancements when the end-to-end distance is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…Such a wake-up system can be used to activate broadband (BB)-PLC systems that in general induce high power consumption [13]. Thus, the power-consuming main PLC systems can be put to power-down mode during standby periods.…”
Section: Introductionmentioning
confidence: 99%